Literature Review: Kandungan Gizi Antara Daging Ayam Yang Diolah Menjadi Fast Food (Fried Chicken) Dengan Daging Ayam Yang Diolah Menjadi Healthy Food (Ayam Goreng) - Alodia Ceritas Octaviane Pai; Anindyta Tiana Putri; Rizella Rorisroresra; Tyas Citra Aulia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study evaluates the nutritional comparison between chicken meat processed into fast food (fried chicken) and that processed into healthy food. The consumption of fried chicken, as a popular form of fast food, is often associated with high levels of fat, calories, and salt, as well as low fiber content, which may negatively impact health. This review employs a Systematic Literature Review (SLR) approach, drawing on references from national and international journals. Findings reveal that processing techniques, particularly the repeated use of cooking oil, increase saturated and trans fat levels in fried chicken. Conversely, processing chicken into healthy food preserves its macro- and micronutrient content, including essential vitamins and fatty acids. This study recommends opting for healthy food choices to reduce the risk of chronic diseases associated with fast food consumption.